efficacy of three disinfectant formulations against multidrug resistant nosocomial agents (2012)
The current increase in the prevalence of nosocomial infections within the hospital environment despite adequate cleaning and disinfection can be said to be due to the following: (i) ineffectiveness of the various disinfectant formulations used in infection control on the various hospital equipments and wards; (ii) development of resistance to the various chemical disinfectant formulations been used in the hospitals by the various microorganisms. Ten bacteria isolates from different clinical specimens of hospitalized patients identified using standard bacteriological methods and found after screening to be resistant to two or more classes of the antibiotics: cephalosporins, quinolones, Betalactams, nitrofuran, macrolide and an aminoglycoside using the Kirby-Bauer method of disc diffusion test were used in this study. These were subjected to susceptibility testing against three selected disinfectant formulations (Izal, Dettol and Jik) at the manufacturer's dilutions and half the dilutions prescribed on their labels by using agar diffusion method. Out of these clinical isolates used in this study, 5 (50%) and 2 (20%) were resistant to manufacturer's dilution